Characterisation of Phantom Limb Pain in Traumatic Lower-Limb Amputees. (13th December 2021) - Sugawara, André Tadeu; Simis, Marcel; Fregni, Felipe; Battistella, Linamara Rizzo
Abstract : Introduction . There is no diagnosis for phantom limb pain (PLP), and its investigation is based on anamnesis, which is subject to several biases. Therefore, it is important to describe and standardize the diagnostic methodology for PLP. Objective . To characterise PLP and, secondarily, to determine predictors for its diagnosis. Methodology . This is a cross-sectional study involving patients with unilateral traumatic lower-limb amputation aged over 18 years. Those with clinical decompensation or evidence of disease, trauma, or surgery in the central or peripheral nervous system were excluded. Sociodemographic and rehabilitative data were collected; PLP was characterised using the visual analogue scale (VAS), pain descriptors, and weekly frequency. Results . A total of 55 eligible patients participated in the study; most were male, young, above-knee amputees in the preprosthetic phase of the rehabilitation. The median PLP VAS was 60 (50–79.3) mm characterised by 13 (6–20) different descriptors in the same patient, which coexist, alternate, and add up to a frequency of 3.94 (2.5–4.38) times per week. The most frequent descriptor was movement of the phantom limb (70.91%). Tingling, numbness, flushing, itchiness, spasm, tremor, and throbbing are statistically significant PLP descriptor numbers per patient predicted by above-knee amputation, prosthetic phase, higher education level, and greater PLP intensity by VAS (p < 0.05 ). Conclusion . PLP is not a single symptom, but a set with different sensations and perceptions that need directed and guided anamnesis for proper diagnosis.